2022
DOI: 10.1002/pros.24366
|View full text |Cite
|
Sign up to set email alerts
|

An update on the current status and future prospects of erectile dysfunction following radical prostatectomy

Abstract: Background: Radical prostatectomy (RP) and radiation treatment are standard options for localized prostate cancer. Even though nerve-sparing techniques have been increasingly utilized in RP, erectile dysfunction (ED) due to neuropraxia remains a frequent complication. Erectile function recovery rates after RP remain unsatisfactory, and many men still suffer despite the availability of various therapies. Objective: This systematic review aims to summarize the current treatments for post-RP-ED, assess the underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 205 publications
0
7
0
Order By: Relevance
“…However, the treatment outcomes are poor compared with those in the general ED population [ 10 ]. Several studies have now demonstrated the ability of stem cell therapy to improve nerve injury ED and reduce patients’ dependence on PDE5 inhibitors [ 11 ], with therapeutic effects varying by stem cell source (Supplementary Table 1).…”
Section: Stem Cells In the Treatment Of Ed Resulting From Cavernous N...mentioning
confidence: 99%
“…However, the treatment outcomes are poor compared with those in the general ED population [ 10 ]. Several studies have now demonstrated the ability of stem cell therapy to improve nerve injury ED and reduce patients’ dependence on PDE5 inhibitors [ 11 ], with therapeutic effects varying by stem cell source (Supplementary Table 1).…”
Section: Stem Cells In the Treatment Of Ed Resulting From Cavernous N...mentioning
confidence: 99%
“…In an animal study, ADSC-derived exosomes and bone marrow-derived, and MSC-derived exosomes reduced pathological alterations in neural anatomy, smooth muscle atrophy, endothelial injury, and collagen deposition. 68 Combining ICI of marrow-derived MSCs and oral-long term administration of PDE5i tadalafil seems to be superior in preserving the CC and endothelial tone while maintaining EF after CNI. Given a low-risk safety profile, SCT and PDE5i suggest a potential role for this dual strategy in the management of PR.…”
Section: Penile Rehabilitation Interventionsmentioning
confidence: 99%
“…have shown that human placental stem cell treatment significantly increased in vivo erectile responses and markers of nerve, endothelial, and smooth muscle cells at the end of the 6th and 12th week in rats. 68 Due to ethical concerns, further translational research has yet to be studied in an RCT. Several positive studies for post-RP ED include intracavernous bone marrow-mononuclear cells and adipose-derived stem cells (ADSC) via ICI.…”
Section: Penile Rehabilitation Interventionsmentioning
confidence: 99%
See 2 more Smart Citations